Experimental verification of a methodology for Monte Carlo modeling of multileaf collimators using the code Geant4 (Brazilian Journal of Radiation Sciences (BJRS), 2018)
Among the many algorithms developed for evaluation of dose distributions in radiotherapy, the Monte Carlo methods provide more realistic results. In intensity modulated radiation therapy, significant differences in dose distributions within the fields defined by the multileaf collimator (MLC) could have significant radiobiology effects. Thus, it is important to model thoroughly the MLC to allow more accurate radiotherapy delivery. The objective of this work is to describe and to validate a methodology for modeling of MLCs using code Geant4. The Varian Millennium 120-leaf MLC was modeled using this methodology and it was experimentally verified. The leaves of the MLC were built using three types of solid (G4Box, G4Tubs and G4ExtrudeSolid) and the Boolean operation of subtraction (G4SubtractionSolid). Based on this methodology, it is possible to simulate other Varian MLC models using Geant4 or other MC code.